A NEW PARADIGM OF CRIMINALIZATION THROUGH THE CONCEPT OF JUDICIAL PARDON BASED ON THE PRINCIPLES OF JUSTICE AND LEGAL UTILITY - Muhammad Arman; Megawati Barthos (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
Judicial pardon empowers adjudicators to absolve defendants—proven guilty through evidence—without sentence imposition, as enshrined in Law Number 1 of 2023 on the Indonesian Criminal Code. This study adopts a normative juridical methodology incorporating statutory and conceptual analyses. Findings demonstrate that judicial pardon provisions signal penal reform toward a humane, proportionate, and substantively just criminal framework. Via this tool, judges may weigh elements like offender culpability, act motivation, personal context, and societal effects. Furthermore, judicial pardon upholds legal utility, acknowledging scenarios where criminalization yields scant benefit to perpetrator, victim, or community. Thus, its integration into the new Criminal Code advances a sanctions system balancing retribution with justice, humanity, and pragmatic value in penal application.